2020
DOI: 10.1007/s11239-020-02170-z
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care platelet function tests: relevance to arterial thrombosis and opportunities for improvement

Abstract: Studies using whole blood platelet aggregometry as a laboratory research tool, provided important insights into the mechanism and modulators of platelet aggregation. Subsequently, a number of point-of-care (POC) platelet function tests (PFTs) were developed for clinical use, based on the concept that an individual’s thrombotic profile could be assessed in vitro by assessing the response to stimulation of platelet aggregation by specific, usually solo agonists such as adenosine diphosphate (ADP), collagen and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 77 publications
(99 reference statements)
2
24
1
Order By: Relevance
“…We identified 4080 citations of which 167 were retained for full-text evaluation. Seven articles [ [23] , [24] , [25] , [26] , [27] , [28] , [29] ] (41,768 patients) reported the rate of VTE in COVID-19 cohorts compared to non-COVID-19 cohorts ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 4080 citations of which 167 were retained for full-text evaluation. Seven articles [ [23] , [24] , [25] , [26] , [27] , [28] , [29] ] (41,768 patients) reported the rate of VTE in COVID-19 cohorts compared to non-COVID-19 cohorts ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…36,36,49,67,76,97,99,[116][117][118][119][120][121][122] By comparing the results obtained from the study, it was concluded that VASP phosphorylation assay, VerifyNow P2Y12 assay, and LTA with 20 µmol/L ADP are ideal PFTs to monitor clopidogrel responsiveness. 54,66,70,117,124 When compared with LTA, VASP-P assay was more suitable 125 and out of LTA, Multiplate assay, Verify Now assay, and TEG, Multiplate assay was found to be ideal to monitor the clopidogrel. 126 Limitations of LTA has paved the way for the development of standardized PFTs such as PFA-100, Multiplate, and VerifyNow P2Y12 assays.…”
Section: Comparison Of the Pf Tsmentioning
confidence: 99%
“…The anticoagulant used must not interfere with the normal physiology of the sample. 54,130 An advanced principle with a simple technique which can be used globally for different agonists without altering the physiological environment of the sample would be ideal. 67 Further, PFT should have the capacity to determine not only platelet aggregation, but also to measure the procoagulant activity of platelets.…”
Section: Sug G E S Ted Improvements For Pl Atele T Fun C Ti On Te Smentioning
confidence: 99%
See 2 more Smart Citations